A study on the relationship between parents’ educational level and their involvement in children’s learning in Johor - Sim, Hui Yee (2023)
This research paper attempted to study the relationship between parents’ educational level and their involvement in children’s learning in Johor. There is limited research investigating the effects of parental education level and parental involvement on young children's learning; thus, the present study is required to examine the relationship from a local context perspective. This study applies Bronfenbrenner’s Ecological Systems Theory to investigate the relationship between parents’ educational level and parental involvement. The quantitative research method and correlational research design were applied in the present study. The research instrument used is the Family Involvement Questionnaire-Short Form (FIQ-SF). Purposive sampling was used, and 72 parents in Johor with children between the ages of 4 and 6 have participated in this study. The current finding’s result shows that there is a significant positive relationship between parents’ educational level and home-school conferencing (r=0.383, p=0.001), schoolbased involvement (r=0.487, p=0.001) and home-based involvement (r=0.387, p=0.001). Descriptive analysis reveals that Johor parents showed a low willingness to get involved in school-based activities. Hence, it implied a need to initiate relevant intervention programmes that help improve collaboration between families and schools. The inferential finding has proven that parents’ educational level is significantly positively related to all aspects of parental involvement. Therefore, it alerts the preschool administrators that helping to improve parents’ knowledge and skills can be an effective strategy to increase parental involvement in school. As recommendations, this study suggests producing a multiple-language questionnaire by using the back translation method, employing random sampling techniques to increase the generalizability of the findings, and combining quantitative and qualitative methods to enhance the depthness of this study